1988
DOI: 10.1038/335181a0
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency virus rev trans-activator modulates the expression of the viral regulatory genes

Abstract: The pathogenic human retrovirus human immunodeficiency virus type 1 (HIV-1) encodes two trans-acting nuclear proteins, tat and rev, whose functional expression is essential for viral replication in vitro. The tat protein greatly enhances the expression of both structural and regulatory genes of HIV-1 (linked to the viral long-terminal-repeat promoter element), whereas the rev gene product (previously termed art or trs) has only been shown to be required for the synthesis of structural proteins. Here, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
331
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(345 citation statements)
references
References 25 publications
13
331
0
1
Order By: Relevance
“…3A). It is reported that Rev, a viral protein, is associated with positive modulation of virion production through up-regulation of mRNA transport into the cytoplasm by interaction with its RNA target, the rev-responsive element (50,51). Thus, this dichotomous effect of HU on HIV activation suggests that HU/IL-6 may enhance the Rev/rev-responsive element (RRE) posttranscriptional pathway, whereas HU/TNF-␣ may interfere with the Rev/RRE elements.…”
Section: Discussionmentioning
confidence: 99%
“…3A). It is reported that Rev, a viral protein, is associated with positive modulation of virion production through up-regulation of mRNA transport into the cytoplasm by interaction with its RNA target, the rev-responsive element (50,51). Thus, this dichotomous effect of HU on HIV activation suggests that HU/IL-6 may enhance the Rev/rev-responsive element (RRE) posttranscriptional pathway, whereas HU/TNF-␣ may interfere with the Rev/RRE elements.…”
Section: Discussionmentioning
confidence: 99%
“…The CXCR4-tropic HIV-1 molecular clone pR8 lacking env (pR8⌬Env) was obtained from Dr. D. Trono (University of Geneva, Switzerland). The pcRev plasmid (34) and the pMM310 plasmid expressing BlaM-Vpr (35) were obtained from the AIDS Research and Reference Reagent Program, National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-1 pseudoviruses bearing HXB2, Bal26, and R3A envelope glycoproteins and the b-lactamase-Vpr chimera (BlaM-Vpr) were produced by cotransfecting HEK293T/17 cells with the HIV-based pR8DEnv packaging vector, pMM310 plasmid expressing BlaM-Vpr, 47 pcRev, 48 and the vector encoding HXB2 Env 49 or Bal26 (a gift from P. Clapham, University of Massachusetts, Worchester, MA) or R3A (a gift from Dr. J. Hoxie, University of Pennsylvania, Philadelphia, PA), using the jetPRIME Ò transfection reagent (VWR, Radnor, PA). The transfection medium was replaced with fresh DMEM/ 10% FBS after 12 h and cells were cultured for 36 h, after which time the virus-containing culture medium was collected, passed through a 0.45-mm filter, aliquoted, and stored at -80°C.…”
Section: Virus Productionmentioning
confidence: 99%